Men´s reproductive alterations caused by bisphenol A and its analogues: a review - Jambor, T; Knížatová, N; Lukáč, N (Physiological research, 2021)
Male reproductive functions are an important area affecting men´s overall health and well-being. However, during the last years, there has been observed increasing incidence of male reproductive issues. The radical growth has been recorded parallelly with a massive expanse of industrialization and agricultural chemigation. Many groups of experts have begun to identify several potential factors and substances that may have adverse effects on men´s reproductive health. Since then, xenobiotics have become a major concern of many scientific studies. There is evidence that most of them have multigenerational and transgenerational effects on reproductive health, which is a serious problem for our population. Bisphenol A could be considered as one of the most studied endocrine disruptors. Until now, several negative effects of bisphenol A were associated with reduced weight testes, histological alterations, impairment spermatogenesis, and steroidogenesis as well as with testes or prostate cancer. Due to convincing evidence, bisphenol A has been started to replace by its analogues such as bisphenol B, S, F, in order to eliminate and suppress the risk of exposure to bisphenol A. However, it seems that a lack of toxicological analyses allows using of these hazardous substances in daily life. Their harmful effect was confirmed by the animal in vitro and in vivo models, while the epidemiological studies monitoring the impact of bisphenol analogues on men's reproductive health are markedly limited. This review provides information about the effects of bisphenol on reproductive health in men. At the same time, it is focused on physiological aspects of sperm viability, steroid hormone secretion, sperm motility, or testes histology in relation to bisphenols exposure.
Keywords: spermatogeneze; benzhydrylové sloučeniny; Endocrine Disruptors; endokrinní disruptory; Male; Benzhydryl Compounds; Animals; Phenols; lidé; Spermatogenesis; mužské pohlaví; testis; Testis; fenoly; Humans; Sperm Motility; zvířata; motilita spermií